Performance of steel frames with new lightweight composite infill walls under curvature ground deformation. (September 2019) - Xie, Wei; Xia, Junwu; Zheng, Yuying; Wang, Qiufen; Chang, Hongfei; Yang, Shangtong
Abstract: In this paper, the structural performance of steel frames with novel lightweight composite infill walls is experimentally and numerically investigated under curvature ground deformation, which is a common consequence of ground mining activities that can cause significant effects on structures and buildings in these areas. A new structural form that combines steel frames and lightweight composite infill walls has recently been used; its performance under curvature ground deformation is of great interest but still not entirely clear. This study compares the mechanical behavior of the open-frame, the closed-frame with mudsill, and the closed-frame with infill walls, through experimental testing under positive and negative curvature ground deformations. Structural responses such as basement counterforce, additional strains at different key locations, and effects of mudsill and infill walls are evaluated. In addition, 3D finite element models are established to simulate the performance of the tested samples and are validated by comparing the results against those from experiments. After validation, the numerical model is applied to a few complex structures incorporating the composite infill walls to investigate their structural performance under both positive and negative curvature ground deformation. It has been found that steel frames with the new composite infill walls can considerably increase the stiffness of structures in resisting ground deformation and re-distribute the loads amongst the beam and column members in the frame. Failure modes for the structures can also be changed by shifting the most dangerous ones from the upper part of the frame to the lower part. Moreover, it has been found that the vertical force of the infill walls is more sensitive to curvature ground deformation than the horizontal force. Further, the influence of the infill wall on the column is more significant, in comparison to that on the beam of the frame. Highlights: Structural performance of steel frames with novel infill walls is experimentally and numerically investigated. The new composite infill walls can considerably increase the stiffness of the structures and re-distribute the loads. The failure modes for the structures can be changed by shifting the most dangerous parts. The vertical force of the infill walls is more sensitive to curvature ground deformation than that in horizontal direction.